Agility in international fast fashion retailing - Räisänen, Raisa (My University, 2013)
The birth of Internet technologies, the developments of fast fashion and multiple retailing channels have created a need for a new, more integrated way for doing retailing. Agility in fast fashion retailing could be seen as a significant way of responding to these changes and furthermore, as a way to respond to consumers’ altering demands. The purpose of this study was to explore the ways in which agile supply chains and integrated multichannel retailing influence the international fast fashion retailing. A framework for agility in retail was developed based on available theoretical considerations in distribution and communication channels. Qualitative research methods and qualitative content analysis were used. Four expert interviews were carried out to gain new perspectives to the objectives. The rest of the data was collected from an industry specific document, expert video and two expert lectures. Following the data collection, the research material was analyzed with qualitative content analysis. The empirical findings on agility in retail were presented based on a coding frame. It was found that agility in retail has multiple parts, which are overlapping and affecting one another. Furthermore, instead of viewing the agile supply chain and integrated multichannel retailing separately of each other as usual, it was found that they should be integrated, and the term “agility” was proposed to denote this approach. Also, it was found that the most common drivers and constrains of integrated multichannel retailing were the new Internet technologies and customer demand. Brick-and-mortar store, online store, mobile devices and social media were found to be the most common retailing channels. Furthermore, in-store technology, click-and-collect approach, NFC-buying, RFID-technology as well as 3D- digital simulations on fabrics and patterns will enhance agility even more in the future. In addition, environmental issues, customer experiences and communication will be important factors. This study has provided new practical insights for the future retailing. Furthermore, it has contributed to the academic research by discussing the traditional approaches of agility in fast fashion retail and bringing in new insights.